The Marburgvirus-neutralizing human monoclonal antibody MR191 targets a conserved site to block virus receptor binding - King, Liam B. (Cell Host Microbe, 2018)
Since its first identification 50 years ago, Marburgviruses have emerged several times, with 83–90% lethality in the largest outbreaks. Although no vaccines or therapeutics are available for human use, the human antibody MR191 provides complete protection in nonhuman primates when delivered several days after inoculation of a lethal marburgvirus dose. The detailed neutralization mechanism of MR191 remains outstanding. Here we present a 3.2 Å crystal structure of MR191 complexed with a trimeric marburgvirus surface glycoprotein (GP). MR191 neutralizes by occupying the conserved receptor-binding site and competing with the host receptor Niemann-Pick C1. The structure illuminates previously disordered regions of GP including the stalk, fusion loop, CX(6)CC switch, and an N-terminal region of GP2 that wraps about the outside of GP1 to anchor a marburgvirus-specific “wing” antibody epitope. Virus escape mutations mapped far outside the MR191 receptor-binding site footprint suggest a role for these other regions in the GP quaternary structure.